Geomorphology of Naples and the Campi Flegrei: human and natural landscapes in a restless land. Issue 4 (28th July 2021) - Ascione, Alessandra; Aucelli, Pietro P.C.; Cinque, Aldo; Di Paola, Gianluigi; Mattei, Gaia; Ruello, Maria; Russo Ermolli, Elda; Santangelo, Nicoletta; Valente, Ettore
ABSTRACT: Naples and its surroundings are a very young landscape, originated from 40 ka in response to strong and explosive volcanic processes, which created the Campi Flegrei, one of the largest volcanic fields of the world. Despite the repeated and continuous volcanic activity, this territory was selected for human settlements since Neolithic times and hosted some of the most important Greek and Roman towns in the Mediterranean area (e.g., Cuma, Parthenope, Neapolis, Baia and Puteoli). Geoarcheological data and historical chronicles testify to human coexistence with eruptions, bradyseismic ground motions, coastline changes, floods and landslides. With the aim of describing the geomorphological evolution of this area to a wide audience, including also non-experts, we constructed a synthetic geomorphological map of the area and sketches that synthesise the main stages of the geomorphological evolution of the historical centre of Naples and the coastal belt of the Gulf of Pozzuoli during the last millennia.